Development of the Cross-Sector GLS Study Program in 104203 Bandar Khalipah Public Elementary School - Flora Siahaan; Khairil Ansari; Zulkifli Matondang (BIRCU, 2020)
This study is aimed to describe the process of developing enrichment books in the learning phase of the school literacy movement. The feasibility of enrichment books on the school literacy movement for students in class VI with the theme of saving sentient beings, and describing the use of enrichment books in the school literacy movement of the learning phase. This study refers to the Borg & Gall development model. The results showed that: (1) the development of enrichment books is based on research and gathering preliminary information, planning, initial product development, validation of material content, design and language, product revisions, assessments with suggestions of class teachers and students, revisions, individual trials, revisions back, small group trials, next revisions, limited field trials, revisions more until the product is valid and suitable for used; (2) the results of the material expert validation included the feasibility of the contents with an average of 90.62% on the “very good” criteria, the feasibility of serving with an average of 95% on the “very good” criteria, and the aspect of graphic with an average of 100% on the “very good” criteria, the average of all aspects is 95.20% on the “very good” criteria, design expert validation with an average of 90.47% on the “very good” criteria, and linguist validation 82% on the “very good” criteria, and (3) the use of enrichment books fulfills the requirements and effectively used as reading material. The results of teacher assessment responses for the enrichment books developed have an average total percentage of 907, 32% with the criteria of